Living in the minds of others: How pudor and social judgements affect women's cervical cancer screening uptake in Mozambique? - Fulane, G.; Major, M.; Lorenzoni, C. (International Journal of Health Planning and Management, 2024)
Mozambique introduced its cervical cancer screening programme in 2009, but only 3.5% of the target women participate in screening annually. While previous research has focused on provision and access to service, and women's cognitive barriers to screening, this study explores the emotional factors, particularly pudor, that affect women's acceptance of screening. Using an institutional work perspective, we conducted an explanatory case study involving documental analysis and primary data collection through semi-structured interviews, focus group discussions, direct observations, and informal conversations with 121 participants, including women, health professionals, and family members from Xai-Xai in Southern Mozambique. Our findings reveal that pudor, an emotion tied to a deep-seated sense of reserve rooted in patriarchal culture and masculine dominance, plays a significant role in limiting women's motivation to participate in screening. This emotion, shaped by social and cultural norms around privacy, intimacy, and sexuality, leads women to view cervical cancer screening as culturally unacceptable, often responding with attitudes emphasising modesty and avoidance. These findings underscore the importance of addressing emotional factors in health care strategies and considering the sociocultural context that influences health behaviours.